2005
DOI: 10.1007/s00280-005-0159-4
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil can cross brain–blood barrier and cause encephalopathy: should we expect the same from capecitabine? A case report on capecitabine-induced central neurotoxicity progressing to coma

Abstract: Literature on fluoropyrimidine-related neurotoxicity will also be reviewed and possible mechanisms of the drug or its metabolites crossing the blood-brain barrier will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…Similarly, small amounts of 5FU cross the BBB (Bourke et al 1973;Soni et al 2008). While rare, central neurotoxicity associated with 5FU treatment is well defined and presents most commonly as cerebellar dysfunction with ataxia (Formica et al 2006). This toxicity is usually acute and tends to resolve completely within days, though it can also have delayed onset (Formica et al 2006) and appears to be related to the schedule of administration (Verstappen et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, small amounts of 5FU cross the BBB (Bourke et al 1973;Soni et al 2008). While rare, central neurotoxicity associated with 5FU treatment is well defined and presents most commonly as cerebellar dysfunction with ataxia (Formica et al 2006). This toxicity is usually acute and tends to resolve completely within days, though it can also have delayed onset (Formica et al 2006) and appears to be related to the schedule of administration (Verstappen et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…While rare, central neurotoxicity associated with 5FU treatment is well defined and presents most commonly as cerebellar dysfunction with ataxia (Formica et al 2006). This toxicity is usually acute and tends to resolve completely within days, though it can also have delayed onset (Formica et al 2006) and appears to be related to the schedule of administration (Verstappen et al 2003). In addition, patients with a deficiency in dehydropyrimidine dehydrogenase, which is responsible for the breakdown and clearance of 5FU, are at increased risk for developing neurotoxicity (Verstappen et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…18 Five case reports and one case series of capecitabineassociated cerebellar toxicity were identified from a MEDLINE literature search using the keywords capecitabine, cerebellar toxicity, and neurotoxicity. 15,17,[19][20][21][22] Cerebellar ataxia was the sole CNS symptom in two of these cases. 19,22 The other four cases were associated with either toxic encephalopathy or multifocal leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 95%
“…every three weeks. 15 One case of reversible posterior leukoencephalopathy syndrome associated with bevacizumab has also been reported. 16 The onset of drug-induced cerebellar toxicity may be acute, delayed, or insidious.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it could be speculated that TYMS suppressors are prone to cellular injury. When given intrathecally, 5-FU produces neurological disturbances and neuropathological lesions [18] , and it can cross the brain-blood barrier and cause encephalopathy [22] . The patients in this study revealed to be TYMS suppressors showing TSER 3RC/3RC genotype and homogenous deletion of 6 bp, respectively, suggesting that suppressed TYMS expression would contribute to the 5-FU-related encephalopathy.…”
Section: Discussionmentioning
confidence: 99%